(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The Document is the result of a disciplinary discussion that the Authors – legal scholars and professionals with long-standing experience in the related topics – decided to open on the main legal end-of life issues raised by Order no. 207/2018 of the Italian Constitutional Court, which declared the absolute ban on assisted suicide unconstitutional under certain conditions and called upon the Parliament to regulate the subject. Starting from the “personalist” and “pluralist” principles, as well as from the principles of equality and self-determination enshrined in the Italian Constitution, the Document offers a “constitutionally oriented” and scientific grounded understanding of the wider concept of “medical assistance to die”. The Document therefore includes some operational proposals on a huge number of tricky issues, such as the prerequisites and conditions to have access to assisted dying, the healthcare professionals involved, the role of the National Healthcare Service, a clear and well-structured procedure, the regulation of conscientious objection, as well as on issues concerning the source of law to be chosen, the related financial coverage, and the relationships and coordination with other legal rules, including the codes of professional ethics.